دراسة المقارنة البنية النحوية في تعليم اللغة العربية في الجامعة الإسلامية الفلاح السنية كنتشونج جمبر - Kafi, Fina Aunul (Al-Fusha : Arabic Language Education Journal, 2018)
In teaching Arabic a teacher needs special ways that can facilitate students to receive lessons. This particular method is based on the educational background of students, age, social, culture, factors of need and so forth. To formulate it, a comparative study between student language and the second language is studied. This formulation is very helpful for students in understanding and applying Arabic, which begins with a comparative study of the syntax of the two languages. This qualitative descriptive research results in the conclusion that students are able to apply certain sentences easily because the elements of similarity are preferred in learning them.